The Benefits of Myrmecochory: A Matter of Stature. (8th April 2015) - Leal, Inara R.; Leal, Laura C.; Andersen, Alan N.
Abstract Myrmecochory, or seed dispersal by ants, occurs widely in angiosperms, and particularly in temperate forest herbs in the northern Hemisphere and sclerophyll shrubs in Mediterranean‐climate landscapes. The lipid‐rich elaiosome on the seed provides nutrition to the ants; however, how the plant benefits from myrmecochory remains unclear. Here, we provide the first comprehensive analysis of the Euphorbiaceae species in the semi‐arid Caatinga vegetation region of northeastern Brazil, and show that myrmecochory strongly associates with small plant stature, even after controlling for seed size. The association of myrmecochory with small stature suggests that the primary benefit to plants concerns distance of dispersal, which reduces parental and sibling competition.